Antimalarial activity of quinoline thiosemicarbazones: synthesis and antiplasmodial evaluation - Nqeno, Lukhanyiso Khanyisile (Rhodes University, Faculty of Science, Department of Chemistry)
Africa is one of the regions that is most affected by malaria, as 90% of all malaria deaths occur in sub-saharan Africa. Malaria is a life threatening disease responsible for an estimated 800000 deaths each year, the majority of these deaths occurred in children under the age of five. The disease is a mosquito-borne, and it is transmitted to humans by the female Anopheles mosquito. The parasite responsible for this disease belong to the Plasmodium genus with Plasmodium falciparum causing the most severe cases of the disease in humans. The most widely available anti-malarials were designed to specifically target the pathogenic blood stage in humans, however, in order to completely eradicate malaria there is a need for the development of medicines that not only target the pathogenic blood stage of the parasite but also block parasite transmission and eliminate asymptomatic and cryptic hepatic forms of the parasite. Iron chelators have recently gained importance as potent antimalarials, to cause infection nearly all protozoa obtain growth essential iron from their hosts. Iron is required for the development of the parasite. Deprivation of utilizable iron by chelation is a proficient approach to arrest parasite growth and associated infection. Thiosemicarbazones are known iron chelating agents by bonding through the sulfur and azomethine nitrogen atoms. This study is aimed at the identification of thiosemicarbazone based derivatives as possible antimalarial agents. Due to their iron chelation abilities there has been increasing interest in the investigation of thiosemicarbazones as possible antimalarials. During the course of this project, several thiosemicarbazone derivatives were synthesized and their structure confirmed using routine analytical techniques (NMR, FTIR, and HRMS). The synthesized compounds were evaluated in vitro against the chloroquine sensitive strain (3D7) of P. falciparum for antimarial activity. The compounds were also evaluated agsinst Hela cells for overt cytotoxicity. The compounds generally showed poor antimalarial activity. One compound (LKN11) was identified to possess intrinsic and moderate antimalarial activity of 6.6 Î¼M. The compounds were generally not cytotoxic against Hela cell at concentrations of up to 20 Î¼M, with only compound LKN10 showing modest cytotoxic activity of 9.5 Î¼M. This research went on to identify two thiosemicarbazone based derivatives which had a significant effect on HeLa and pLDH cells.
Keywords: Antimalarials; Quinoline; Thiosemicarbazones; Malaria -- Chemotherapy; Plasmodium falciparum; Malaria -- Africa, Sub-Saharan; Iron chelates -- Therapeutic use